Effectiveness of different combinations of DMARDs and glucocorticoid bridging in early rheumatoid arthritis: two-year results of CareRA. (24th June 2019) - Stouten, Veerle; Westhovens, René; Pazmino, Sofia; De Cock, Diederik; Van der Elst, Kristien; Joly, Johan; Verschueren, Patrick; ,
Abstract: Objectives: To investigate whether MTX should be combined with an additional DMARD and bridging glucocorticoids as initial treatment for patients with early RA to induce an effective long-term response. Methods: The Care in early RA study is a two-year investigator-initiated pragmatic multicentre randomized trial. Early RA patients, naïve to DMARDs and glucocorticoids, were stratified based on prognostic factors. High-risk patients were randomized to COBRA-Classic ( n = 98): MTX, sulfasalazine, prednisone step-down from 60 mg; COBRA-Slim ( n = 98): MTX, prednisone step-down from 30 mg; or COBRA-Avant-Garde ( n = 93): MTX, leflunomide, prednisone step-down from 30 mg. Low-risk patients were randomized to COBRA-Slim ( n = 43); or Tight Step Up (TSU) ( n = 47): MTX without prednisone. Clinical/radiological outcomes at year 2, sustainability of response, safety and treatment adaptations were assessed. Results: In the high-risk group 71/98 (72%) patients achieved a DAS28-CRP < 2.6 with COBRA-Slim compared with 64/98 (65%) with COBRA-Classic and 69/93 (74%) with COBRA-Avant-Garde ( P = 1.00). Other clinical/radiological outcomes and sustainability of response were similar. COBRA-Slim treatment resulted in less therapy-related adverse events compared with COBRA-Classic ( P = 0.02) or COBRA-Avant-Garde ( P = 0.005). In the low-risk group, 29/43 (67%) patients on COBRA-Slim and 34/47 (72%) on TSU achieved a DAS28-CRP < 2.6 ( P = 1.00). On COBRA-Slim, low-risk patients had lower longitudinal DAS28-CRP scores over 2 years, a lower need for glucocorticoid injections and a comparable safety profile compared with TSU. Conclusion: All regimens combining DMARDs with glucocorticoids were effective for patients with early RA up to 2 years. The COBRA-Slim regimen, MTX monotherapy with glucocorticoid bridging, provided the best balance between efficacy and safety, irrespective of patients' prognosis. Trial registration: ClinicalTrials.gov, http://www.clinicaltrials.gov, NCT01172639.